Quantification of the immunohistochemical staining of fibroblast activation protein in intrathoracic solitary fibrous tumors using QuPath - Omura, Akiisa; Kimura, Toru; Maniwa, Tomohiro; Watabe, Tadashi; Honma, Keiichiro; Shintani, Yasushi; Okami, Jiro (Surgery today (Tokyo, Japan), 2025)
Purpose Solitary fibrous tumors (SFTs) are rare mesenchymal neoplasms that can develop in the pleura. In the past, SFTs were considered benign, but there have been reports of SFTs being highly malignant. Fibroblast activation protein (FAP) is a serine protease, overexpressed in various cancers, which has been explored as a diagnostic and therapeutic target. We analyzed patients who underwent resection of an intrathoracic SFT, including metastatic pulmonary nodules from extrathoracic organs. Methods The subjects of this retrospective study were seven patients with a primary SFT and two with metastatic SFTs in the lungs. After immunohistochemical staining of the resected tumors, quantification of the stained area was performed using QuPath. Results Immunohistochemical quantification of FAP showed that it was expressed to varying degrees in the intrathoracic SFTs, with higher expression levels observed in metastatic SFTs than in primary pleural SFTs. Pathological examination confirmed the expression of FAP. Conclusion Our results support the potential usefulness of FAP in the diagnosis of intrathoracic SFTs, including metastatic pulmonary nodules.